PENERAPAN ALGORITMA APRIORI DALAM MENENTUKAN POLA PEMBELIAN KONSUMEN DI KAFE HIDDEN TOAST AND FLOAT - Ridwan Rismanto; Lucki Darmawan; Arief Prasetyo (Jurusan Teknologi Informasi Politeknik Negeri Jember, 2019)
Progress in Information Technology encourages culinary businesses to innovate, one of them is a computerized system, online-based sales and several interesting features that can increase consumer interest and increase sales to be the most frequently used innovation today. The cafe